Current clinical status, glucose control, and complication rates of children and youth with type 1 diabetes in Rwanda. Issue 3 (28th December 2012) - Marshall, Sara L; Edidin, Deborah; Sharma, Vineeta; Ogle, Graham; Arena, Vincent C.; Orchard, Trevor
Abstract Objective To describe the clinical status of youth and adolescents (≤ 25 yr) in the Rwanda Life For A Child (LFAC) program who had their first HbA1c measure in 2009 or 2010, and to identify factors which may relate to glycemic control (HbA1c) and complication status. Research Design and Methods: Data were collected from June 2009 to November 2010 for the LFAC program in Rwanda and comprise clinical data from when participants' first HbA1c reading was obtained. Results From June 2009 to November 2010, 286 youth aged ≤25 yr had their first HbA1c. Mean age, duration, and age at diagnosis were 18.6 ± 4.5 yr, 3.4 ± 3.1 yr and 15.1 ± 4.8 yr, respectively. Mean HbA1c was 11.2 ± 2.7% with 15.7% (n = 45) having HbA1c <8%, while 30.8% (n = 88) had HbA1c >14%. Five (2.1%) had either abnormal tuning fork vibratory sensation or monofilament response, 21% (n = 31) had microalbuminuria (MA, A/C ratio >30 mg/g) and 5% (n = 7) had nephropathy (A/C ratio >300 mg/g). Diabetes duration and insulin dose/kg were positively associated with higher HbA1c, while residing in the southern province was associated with lower HbA1c. Duration, diastolic blood pressure, and HbA1c were positively associated with developing MA, while age was protective. Conclusions These data from the LFAC program for 2009–2010 show that there is a urgent need for dramatically improved care, as many patients have greatly elevated HbA1c measures, often >14%. We have identified correlates of better control (e.g., living in the Southern province) and MA (e.g., diastolic blood pressure), which provide potential avenues to improved quality of care.